Immigrants in the classroom and effects on native children - Peter Jensen (IZA World of Labor, 2015)
Many countries are experiencing increasing inflows of immigrant students. This raises concerns that having a large share of students for whom the host country language is not their first language may have detrimental effects on the educational outcomes of native children. However, the evidence is mixed, with some studies finding negative effects, and others finding no effects. Whether higher concentrations of immigrant students have an effect on native students differs across countries according to factors such as organization of the school system and immigrants' socio-economic background.
Keywords: I21; J15; 330; educational performance; immigrant concentration; native children; test scores